Museums and interactive virtual learning - Mitchell, Allyson; Moehring, Tami; Zanetis, Janet ([Place of publication not identified] : Routledge, 2022)
"Museums and Interactive Virtual Learning provides informal educators with practical resources that will help them to build dynamic digital engagement experiences within their own cultural organizations. Presenting vignettes from experienced museum educators and end users, as well as scientific data and practical resources, the book highlights the mutual benefits interactive virtual learning (IVL) programs offer to the museum and those visiting from a distance. Chapters mirror the step-by-step process of developing reputable IVL programs and emphasize how important it is for cultural organizations to encourage cross-departmental collaboration, if they wish to ensure that their programs align with the overall goals of the organization. Providing a thorough overview of the technologies, budget, marketing and staff requirements, the authors offer a realistic depiction of the work involved in building content for digital engagement. Emphasising the importance of assessing existing programming, the book shows how institutions can adapt content to fit a virtual format and create inclusive digital engagement opportunities that reach local, national, and international audiences. Museums and Interactive Virtual Learning is an essential guide for professionals who are tasked with interpreting the content of a cultural organization and building lasting digital engagement opportunities. It will be particularly useful to those looking to reach diverse audiences"--
The history & practice of interactive virtual learning in museums -- The market and audience for IVL in museums -- IVL broadcast environments physical and virtual setups -- IVL program creation -- Staffing and scheduling -- Marketing IVL programs -- Funding and budgeting for the IVL initiative -- Connecting to diverse audiences -- How virtual experiences can impact learning.
OCLC-licensed vendor bibliographic record.
Keywords: EDUCATION / Distance Education & Learning; Museums -- Educational aspects; Interactive multimedia; Shared virtual environments; Computer-assisted instruction